New nonlipid effects of statins and their clinical relevance in cardiovascular disease - Undas, Anetta; Celińska-Löwenhoff, Magdalena; Kaczor, Marcin; Musial, Jacek (Thrombosis and Haemostasis, 2004)
Inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A (HMGCoA) reductase, statins, have been demonstrated to reduce cardiovascular morbidity and mortality in patients with a wide range of cholesterol levels. Numerous cholesterol-independent effects of statins that may limit atherosclerosis are probably related to inhibition of the geranylgeranylation of GTP-binding intracellular signaling proteins and involve: improved vasoreactivity, mostly through increased NO bioavailability; decreased expression of proinflammatory cytokines (interleukin-6, interleukin-1β, tumor necrosis factor α), C-reactive protein, chemokines, matrix metalloproteinases, and tissue factor with the subsequent inhibition of thrombin generation; reduced platelet activity; increased thrombomodulin expression; enhanced fibrinolysis, regulation of angiogenesis and immunomodulation. However, the clinical relevance of multiple protective effects induced by statins has not been clarified yet.
Keywords: Statins; lipids; atherosclerosis